2013
DOI: 10.1017/s0022215113002351
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of clindamycin in reducing pain following tonsillectomy in adults: a double-blind, randomised trial

Abstract: Topical clindamycin was not demonstrated to be more effective than normal saline in the reduction of throat pain following tonsillectomy in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Eight eligible studies [126][127][128][129][130][131][132][133] reported inconclusive pain outcomes with the use of antibiotics. In studies reporting an analgesic effect, two tested antibiotic mouth wash.…”
Section: Other Therapiesmentioning
confidence: 99%
“…Eight eligible studies [126][127][128][129][130][131][132][133] reported inconclusive pain outcomes with the use of antibiotics. In studies reporting an analgesic effect, two tested antibiotic mouth wash.…”
Section: Other Therapiesmentioning
confidence: 99%
“…3 Furthermore, the studies to support topical antibiotics in reducing post-tonsillectomy morbidity are inconsistent and have several biases because of methodological flaws. 53,54 Although some studies show that antibiotics reduce the bacterial count in the post-operative tonsillar fossa, 16,55 a clinical correlation in terms of reduction in morbidity is lacking. Hence, Dhiwakar et al (2012) suggest that post-tonsillectomy complications primarily occur as a result of tissue injury and oedema induced by surgical technique, with minimal or nil additional morbidity conferred by bacterial inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Local perioperative antibiotic prophylaxis remains an open issue, as some recent studies have confirmed reduced pain and postoperative bleeding in patients following local perioperative administration of clindamycin [37]. However, there is also research questioning this concept [38].…”
Section: Discussionmentioning
confidence: 99%